2019
DOI: 10.1210/en.2019-00177
|View full text |Cite
|
Sign up to set email alerts
|

Differential Actions of Estrogen Receptor α and β via Nongenomic Signaling in Human Prostate Stem and Progenitor Cells

Abstract: Human prostate stem and progenitor cells express estrogen receptor (ER)α and ERβ and exhibit proliferative responses to estrogens. In this study, membrane-initiated estrogen signaling was interrogated in human prostate stem/progenitor cells enriched from primary epithelial cultures and stem-like cell lines from benign and cancerous prostates. Subcellular fractionation and proximity ligation assays localized ERα and ERβ to the cell membrane with caveolin-1 interactions. Exposure to 17β-estradiol (E2) for 15 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 75 publications
1
22
0
Order By: Relevance
“…Alternations in estrogenic signaling pathways, as well as ERβ expression, have been discussed in the context of physiological and pathological processes, such as maintenance of the bone marrow microenvironment [ 11 ], neuronal-mediated contractions of the gastrointestinal tract [ 12 ], recovery of reproductive system injury [ 13 ], anxiolytic effects [ 14 ], and diseases such as Parkinson’s disease [ 15 ], endometriosis [ 16 ], myocardial infarction [ 17 ] and type 2 diabetes [ 18 ]. Moreover, ERβ has been shown to participate in the pathological process of various cancers, including uterine leiomyomas [ 19 ], colorectal cancer [ 20 ], desmoid tumors [ 21 ], prostate cancer [ 22 ] and duct carcinoma [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternations in estrogenic signaling pathways, as well as ERβ expression, have been discussed in the context of physiological and pathological processes, such as maintenance of the bone marrow microenvironment [ 11 ], neuronal-mediated contractions of the gastrointestinal tract [ 12 ], recovery of reproductive system injury [ 13 ], anxiolytic effects [ 14 ], and diseases such as Parkinson’s disease [ 15 ], endometriosis [ 16 ], myocardial infarction [ 17 ] and type 2 diabetes [ 18 ]. Moreover, ERβ has been shown to participate in the pathological process of various cancers, including uterine leiomyomas [ 19 ], colorectal cancer [ 20 ], desmoid tumors [ 21 ], prostate cancer [ 22 ] and duct carcinoma [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human prostate CSCs and papillary thyroid CSCs highly express ERβ (114,115). ERβ overexpression in CSCs can promote cancer stemness through estrogen signaling (91,115). Thus, estrogen can directly regulate CSCs by activating ERβ.…”
Section: Regulatory Network Of the Estrogen Axis In Cscsmentioning
confidence: 99%
“…Although most CSCs are ER − ( 10 , 75 ), estradiol can nevertheless increase the number of CSCs, possibly via the non-genomic signaling pathway, which is a regulatory mechanism that does not involve direct binding to DNA and only occurs in the plasma membrane and cytoplasm ( 66 , 83 , 84 ). The non-genomic estrogen signals that regulate CSCs are mainly mediated by cell membrane–associated ERs, including G protein–coupled ER (GPER/GPR30) ( 85 – 87 ), ERα variant ERα36 ( 88 90 ), and ERβ ( 91 ) ( Figure 1 ).…”
Section: Regulatory Network Of the Estrogen Axis In Cscsmentioning
confidence: 99%
“…AR is not the only nuclear receptor that could be involved in the progression of PCa. Hence, Gail Prins' group has shown that early exposure to estrogens and estrogen-like compounds could also increase PCa incidence through ERα [30,31].…”
Section: The Activity Of Androgens and Estrogensmentioning
confidence: 99%